Faktor-faktor Penentu Keberhasilan Usaha Kecil dan Menengah (UKM) di Kota Yogyakarta - Eny Sulistyowati; Nining Sofiati Lestari (Jurnal Maksipreneur, 2016)
This research was conducted with the aim to explain the influence of the characteristics of the owner/manager of the business strategy, describes the influence of business strategy on business performance, explaining the influence of the characteristics of the owner/manager of the business performance. Variables used in this research is variable owner/manager, business strategy (independent variable) and variable performance or Small Bussinis Performance (dependent variable). The results obtained show that a direct influence on the performance characteristics of the manager of small and medium businesses in the city of Yogyakarta strong with R2 values of 0.224, or 22.4%, the effect of business strategies on business performance of small and medium businesses in urban areas with R2 values of 0,049 or 4.9%. Meanwhile, indirectly influence the characteristics of managers' business performance through business strategy in the city of Yogyakarta only has value R2 value of 0.080 or 8.0%.